Influence Of Pouring Temperatures To Fluidity Of Aluminium Scrap Cans With Investment Casting Using Natural Clays As Mould Materials - Rahmat Rosandi; Dedy Masnur (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Pekanbaru area produced scrap of beverage cans; an average of 4.5 tons per month by a scrap collector and it will increase every time. The Pekanbaru area also has natural clays, which can be used as mold material for investment casting. Processing of aluminum cans into a product using the natural clays as a mold in investment casting method will add the economic value of aluminum scrap cans. Study of fluidity is necessary to obtain usable information before creating of cast part design. This research aims to investigate the influence of pour temperatures to fluidity for the aluminum scrap cans casting, in natural clays. In this research used the pouring temperature variables: 650oC, 700oC and 750oC. Results showed the fluidity at pour temperatures of 650oC, 700oC, and 750oC approximately of 213.88 mm, 292 mm, and 360.97 mm, respectively. Results also showed that the fluidity was increased as well as increasing the pour temperatures. The fluidity increased 78.12 mm or 36.52% at pour temperatures of 650oC to 700oC, and it increased 68.97mm or 23.62% at pour temperatures of 700oC to 750oC.Keywords: fluidity, temperature, cast aluminum cans